2020
DOI: 10.1002/cpt.2041
|View full text |Cite
|
Sign up to set email alerts
|

Local Transdermal Delivery of Telapristone Acetate Through Breast Skin, Compared With Oral Treatment: A Randomized Double‐Blind, Placebo‐Controlled Phase II Trial

Abstract: Oral breast cancer prevention medications entail systemic exposure, limiting acceptance by high‐risk women. Delivery through the breast skin, although an attractive alternative, requires demonstration of drug distribution throughout the breast. We conducted a randomized double‐blind, placebo‐controlled phase II clinical trial comparing telapristone acetate, a progesterone receptor antagonist, administered orally (12 mg/day) or transdermally (12 mg/breast) for 4 ± 1 weeks to women planning mastectomy. Plasma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Thorough tissue distribution of drugs locally delivered is restricted by a limited tissue penetration distance, with solubilizers and permeation enhancers being proposed to increase tissue penetration . Although fenretinide tissue distribution was not determined here, a previous study demonstrated a similar relative distribution of telapristone acetate across sampling sites in women breasts when administered topically to the breast skin compared to its oral administration, with subcutaneous fat and deep (closer to muscles) sites having the highest concentration. The authors suggested that the fatty envelope of the breast might serve as a reservoir for prolonged drug distribution aided by the mammary lymphatic circulation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thorough tissue distribution of drugs locally delivered is restricted by a limited tissue penetration distance, with solubilizers and permeation enhancers being proposed to increase tissue penetration . Although fenretinide tissue distribution was not determined here, a previous study demonstrated a similar relative distribution of telapristone acetate across sampling sites in women breasts when administered topically to the breast skin compared to its oral administration, with subcutaneous fat and deep (closer to muscles) sites having the highest concentration. The authors suggested that the fatty envelope of the breast might serve as a reservoir for prolonged drug distribution aided by the mammary lymphatic circulation.…”
Section: Discussionmentioning
confidence: 87%
“…22 Second, previous studies demonstrated that topical drug administration to the breast skin (thus, in close proximity to the mammary tissue) resulted in similar breast distribution compared to oral administration but lower plasma levels. 28 Finally, subcutaneous administration of fenretinide-loaded PLGA implants placed alongside of oral squamous cell carcinoma tumors inhibited tumor xenographs with local controlled release, supporting the applicability of local fenretinide administration for chemoprevention. 27 In this study, a phosphatidylcholine (PC)-based nonaqueous ME was developed as a precursor formulation for injection.…”
Section: Introductionmentioning
confidence: 88%
“…To date, transdermal delivery of chemopreventative drugs (such as the tamoxifen metabolite 4-hydroxytamoxifen and chemotherapeutic agents (including dasatinib and docetaxel) have been extensively explored in murine models with promising results [ 79 , 80 ]. Additionally, human clinical studies have confirmed this mode of drug delivery leads to a sharp restriction in plasma levels of the drugs, which would most likely reduce systemic side effects, as well as having drug distribution within the breast equivalent to oral dosing [ 81 , 82 ]. One of the challenges with local transdermal delivery of drugs is the properties of the drugs themselves, with some drugs not readily permeating the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Like afimoxifene and endoxifen gel, the investigators found that effective telapristone acetate levels could be achieved in the mammary tissue (127). A recently published phase II trial comparing oral to transdermal delivery of telapristone acetate in women undergoing mastectomies confirmed that local drug distribution patterns were similar between treatment groups, establishing the feasibility of topical telapristone acetate for breast cancer prevention in high-risk women (128). A summary of these trials can be found in Table 3.…”
Section: Selective Progesterone Receptor Modulatorsmentioning
confidence: 98%